The Effect of Teams Games Tournament Method Assisted by Card Sort Media to Improve Student Creative Thinking Skill - Karisma, Rosa; Nizaar, Muhammad; Haifaturrahmah, Haifaturrahmah (Universitas Ahmad Dahlan, 2024)
This research aims to determine the influence of the Teams Game Tournament (TGT) method, assisted by card sort media, on enhancing creative thinking skills among fourth-grade students. The research design employed in this study is a quasi-experimental design with a pre-test and post-test design. The research was conducted at SDN 15 Mataram, with a population of 40 fourth-grade students from two classes, consisting of 20 students in each class. The researchers used random sampling to select the experimental group and the control group, drawing lots conducted by the class teacher using a lottery system. Data collection methods in this study involved both test and non-test techniques. Based on the results of the data analysis, it can be concluded that the t-test result (t-value) is 8.692, while the t-table value is 2.042. Since the t-value is greater than the t-table value (t-value > t-table), the null hypothesis is rejected, and the alternative hypothesis is accepted. This indicates that the cooperative learning model of the make-a-match type can improve creative thinking skills among fourth-grade students.